Dampak Mental Exhaustion Terhadap Perilaku Sosial Remaja - Rusyda, Arina Ilfa; Armalita, Rani (Batanang : Jurnal Psikologi, 2023)
Adolescence is a transition from childhood to adulthood. At this time adolescents are very vulnerable to changes that occur, one of which is a change in social behavior. In social behavior, adolescents are influenced by their own mentality. Very often teenagers are faced with problems in life so that they experience mental exhaustion. This mental exhaustion will boomerang for teenagers in social interaction, more precisely in adolescent social behavior. This study uses the method of literature review or literature review. This study shows that mental exhaustion has a major influence on adolescent social behavior such as forming negative social behavior.Keywords: mental exhaustion, social behavior, adolescence